The effect of social presence, mobile phone usage, and trust on venture success in Johannesburg - Ncube, Tinahe Mbisana (My University, 2017)
The study investigates the relationship social presence has on venture performance through the use of mobile devices for Johannesburg based small to medium business ventures. The study touches on the concept of social presence and aims to evaluate how business network trust and social presence influence the success of SMME’s in Johannesburg. This study aims to help entrepreneurs understand how to leverage the benefits of using their social presence and to aims to understand how to use mobile phone technology benefit their ventures. This paper is equally important to researchers who are interested in the field of social presence and mobile technology.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree Master of Management specializing in Entrepreneurship and New Venture Creation, August 2017
Keywords: Mobile communication systems; Information technology--Social aspects